Molecular dynamics study of pressure-driven water transport through graphene bilayers - Liu, Bo (2016)
The pressure-driven water transport inside the nanochannel formed by GE bilayers is studied via molecular dynamics simulation. The effects of flow driving pressure and channel size, as well as interaction strength between the water molecules and the GE bilayer are investigated and understood by exploring the distribution of the water molecules, their average velocity, and the friction between them and the channel walls. Ultrafast water flow rate is observed and different channel size dependences of the water flow rate are discovered for weak and strong interaction strengths. The layered water structure inside the GE bilayer is found to play a significant role in influencing the water flow rate. This study is of significance for the design and application of GE-based nanomaterials in future nanofiltration and water purification technologies.